The relationship between overweight and female infertility - Costa, Maíra Masello da; Andrade, Caroline Brandão; Soares, Francisca Valdenia Guerreiro; Belfort, Gabriella Pinto (HSJ, 2021)
Excessive weight seems to negatively influence fertility, and as it is a modifiable factor, understanding this relationship can contribute to infertility treatment. Adipose tissue is responsible for releasing several hormones and cytokines related to the reproductive system, such as leptin, TNF-a, and Interleukin-6, substances that can negatively impact female fertility. Additionally, a woman's diet and lifestyle can influence body weight and fertility. Food consumption, characterized by a high intake of foods with high energy density, high levels of sugar, saturated fat, and poor nutrients, as well as physical inactivity, can favor excessive weight. Thus, losing body weight obtained through a healthy diet associated with physical activity may restore fertility in overweight women.